Determination of chlorpropham (CIPC) residues, in the concrete flooring of potato stores, using quantitative (HPLC UV/VIS) and qualitative (GCMS) methods. (March 2018) - Douglas, Leisa; MacKinnon, Gillian; Cook, Gordon; Duncan, Harry; Briddon, Adrian; Seamark, Steven
Abstract: Isopropyl-N-(3-chlorophenyl) carbamate (CIPC, common name Chlorpropham) is commonly used for post-harvest sprout inhibition in stored potatoes. It is applied as a thermal fog which results in loss to the fabric of the store and the atmosphere. Recently, there have been concerns in the United Kingdom because of cross contamination of other crop commodities that were stored in buildings with a history of CIPC usage. This cross contamination may have occurred because of retained residues in the fabric of the stores. The retention of CIPC in concrete is poorly understood; therefore the requirement for a robust analytical method for the detection and quantification of CIPC in concrete is a critical first step in tackling this problem. A method using High-Performance Liquid Chromatography with ultraviolet detection (HPLC UV/VIS) was validated. CIPC recoveries at three concentration levels (0.4, 4.0 and 40.0 μg g −1 ) were in the range of 90.7–97.0% with relative standard deviations between 2.14 and 3.01%. The limits of detection and quantification were 0.03 and 0.1 μg g −1, respectively. This study confirmed that CIPC was persistent in concrete to a depth of 4 cm, with >90% within the top 1 cm of the flooring. Highlights: CIPC is lost to the concrete fabric of potato stores during application. HPLC UV/VIS method developed and validated to detect CIPC in concrete. CIPC presence in concrete confirmed by GCMS. CIPC is persistent in the concrete flooring of potato stores at 4 cm depth. Top 1 cm of flooring contains >90% CIPC.